Ferrite pre-sintered body and method for producing ferrite sintered magnet
By adding a specific amount of spinel-type ferrite phase and Mn to the pre-sintered ferrite sintered magnets, the problem of insufficient magnet characteristics of the existing ferrite sintered magnets is solved, and the improvement of high-performance magnet characteristics is achieved. Suitable for industrial motors and electric vehicle drive motors and other applications.
Patent Information
- Application Number
- CN202411525062.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-02-23
- Filing Date
- 2022-03-21
- Publication Date
- 2025-01-07
AI Technical Summary
The existing ferrite sintered magnets are insufficient in high-performance applications, especially in industrial motors and electric vehicle drive motors, with low coercive force (HcJ) and cannot meet the high-performance needs.
Ferrite sintering is formed by using a ferrite pre-calcined body containing a specific amount of spinel-type ferrite phase, by adding spinel-type ferrite phase and Mn to the pre-calcined body after the solid phase reaction is completely completed. Magnet, optimize its magnet characteristics.
The magnet characteristics of ferrite sintered magnets are improved, including residual flux density (Br) and coercive force (HcJ), making them suitable for high-performance motors and electric vehicle drive motors.
Smart Images

Figure BDA0005108989560000121 
Figure BDA0005108989560000141 
Figure BDA0005108989560000151
Abstract
Description
[0001] This case is filed on March 21, 2022 、Application No. 202210276120.9 , the invention is named “ Ferrite Method for producing calcined body and sintered ferrite magnet "Divisional application Technical Field
[0002] The invention relates to a method for manufacturing a ferrite calcined body and a ferrite sintered magnet. Background Art
[0003] Although the maximum magnetic energy product of ferrite sintered magnets is only 1 / 10 of that of rare earth sintered magnets (such as NdFeB sintered magnets), since the main raw material is cheap iron oxide, it has excellent cost performance and has very stable chemical properties. Therefore, it is used in various applications such as various motors and speakers, and is still the world's largest produced magnet material by weight.
[0004] Among the various applications of sintered ferrite magnets, such as motors and speakers, the demand for high-performance materials is particularly strong in motors for automotive electrical equipment and home appliances. In recent years, against the backdrop of soaring prices of rare earth raw materials and the apparent risk of procurement, research has been conducted on the application of sintered ferrite magnets in industrial motors and drive motors and generators for electric vehicles (EV, HV, PHV, etc.), which have only used rare earth sintered magnets so far.
[0005] The typical ferrite sintered magnet is Sr ferrite with a magnetite structure, which is basically composed of SrFe 12 O 19 In the mid-to-late 1990s, SrFe 12 O 19 Part of Sr 2+ La 3+ Replacement, part of Fe 3+ Co 2 + The practical application of substituted Sr-La-Co ferrite sintered magnets (hereinafter also referred to as "SrLaCo magnets") has significantly improved the magnetic properties of ferrite magnets. In addition, in 2007, Ca-La-Co ferrite sintered magnets (hereinafter also referred to as "CaLaCo magnets") with further improved magnetic properties were developed and are currently being put into practical use.
[0006] However, ferrite sintered magnets are generally manufactured through the processes of mixing, pre-sintering, crushing, molding, firing, and processing of raw materials. Generally speaking, "pre-sintering" refers to the process of heating the mixed raw materials to form a ferrite phase (sometimes also called a ferrite compound or M phase) with a hexagonal magnetite (M-type) structure through a solid phase reaction, and the product obtained by pre-sintering is called a "pre-sintered body".
[0007] It has always been considered natural to increase the composition ratio of the ferrite phase (hereinafter sometimes referred to as "phase ratio") in the pre-calcined body stage (preferably 100 mass% = M phase single phase). This is because the ratio of the M phase in the ferrite sintered magnet obtained by crushing, molding and firing the pre-calcined body is also increased, and it is expected to achieve high magnetic properties. In other words, the hematite phase (α-Fe2O3), orthoferrite phase (LaFeO3, etc.) and spinel ferrite phase (such as CoFe2O4, etc.) other than the ferrite phase (M phase) are multiphases, and these multiphases are considered to be best not included in the pre-calcined body.
[0008] Prior art literature
[0009] Patent Literature
[0010] Patent Document 1: Japanese Patent Application Publication No. 2020-155609
[0011] Patent document 1 describes a method for producing a sintered ferrite magnet by using a calcined powder containing 12 to 30 mass % of a hematite phase, 3 to 10 mass % of a La orthoferrite phase, and 5 to 10 mass % of a spinel ferrite phase in a Ca-La-Co ferrite sintered magnet in which a portion of Co is replaced by Zn.
[0012] The invention described in Patent Document 1, in short, is that in a CaLaCo magnet of a specific composition in which the La content is greater than 0.55 in atomic ratio and a portion of Co is replaced by Zn, a calcined body in which the solid phase reaction has not yet been completely completed (the solid phase reaction is still in progress) by low-temperature calcination is used, and trace amounts of SiO2 and CaO are added for molding and sintering, thereby obtaining a product having the same magnetic properties as when a calcined body with the same composition and in which the solid phase reaction has been completely completed by high-temperature calcination is used (Patent Document 1, paragraph 0029, etc.).
[0013] However, according to the invention described in Patent Document 1, in a CaLaCo magnet of a specific composition in which the La content is greater than 0.55 in atomic ratio and a portion of Co is replaced by Zn, a high residual magnetic flux density (hereinafter referred to as "Br") can be obtained, but the coercive force (hereinafter referred to as "H") is low. cJ ”) is low, and the magnetic properties are not sufficient for use in the above-mentioned industrial motors, drive motors for electric vehicles, generators, etc. Summary of the invention
[0014] Technical problem to be solved by the invention
[0015] An object of the present invention is to provide a ferrite calcined body capable of obtaining a ferrite sintered magnet having high magnetic properties, and a method for producing a ferrite sintered magnet using the ferrite calcined body.
[0016] The inventors of the present invention have conducted in-depth research to achieve further high performance of the CaLaCo magnet. As a result, it was found that, contrary to the existing view that the calcined body must be a single phase of the M phase, when a specific amount of spinel ferrite phase is contained in the calcined body after the solid phase reaction is completely completed, the magnetic properties of the sintered magnet made using the calcined body are improved. It was also found that in the spinel ferrite phase containing a specific amount, the content of Mn, which is inevitably mixed as an impurity and may reduce the magnetic properties, is greater than its content in the ferrite phase (M phase). That is, it was found that introducing Mn into the spinel ferrite phase and rendering it harmless has the effect of improving the magnetic properties, and it is no longer a multi-phase in the calcined body, but an indispensable constituent phase.
[0017] Technical solutions for solving technical problems
[0018] That is, the ferrite calcined body of the present invention comprises: a ferrite phase having a hexagonal M-type magnetoplumbite structure containing metal elements of Ca, R, A, Fe and Co (R is at least one rare earth element, La is an element that must be contained, and A is Sr and / or Ba); and a spinel-type ferrite phase containing Co, and the ferrite calcined body contains 70% by mass or more and less than 100% by mass of the ferrite phase and more than 0% by mass and less than 30% by mass of the spinel-type ferrite phase.
[0019] The ferrite calcined body of the present invention may further contain a La orthoferrite phase in an amount of more than 0 mass % and less than 3 mass %.
[0020] The ferrite calcined body of the present invention preferably contains substantially no hematite phase.
[0021] The ferrite calcined body of the present invention preferably contains 5 mass % or more and 30 mass % or less of the spinel ferrite phase.
[0022] The ferrite calcined body of the present invention preferably contains 5 mass % or more and 25 mass % or less of the spinel ferrite phase.
[0023] The ferrite calcined body of the present invention preferably contains 10 mass % or more and 20 mass % or less of the spinel ferrite phase.
[0024] In the ferrite calcined body of the present invention, it is preferred that Mn is contained in the calcined body, and the Mn content in the spinel ferrite phase is larger than the Mn content in the ferrite phase.
[0025] In the ferrite calcined body of the present invention, it is preferred that Mn be contained only in the spinel ferrite phase.
[0026] In the ferrite calcined body of the present invention, it is preferred that the spinel ferrite phase contains Ca, Fe, Co and Mn, and when the total amount of the above elements is 100 at %, the composition ratio is:
[0027] Ca: more than 0 at% and less than 10 at%,
[0028] Fe: 80 at% or more and 90 at% or less,
[0029] Co: 2 at% to 15 at% and
[0030] Mn: more than 0 at % and 5 at % or less.
[0031] In the ferrite calcined body of the present invention, it is preferred that when the total amount of Ca, R, A, Fe and Co in the ferrite phase is 100 at %, the composition ratio is:
[0032] Ca: 2.0 at% or more and 6.5 at% or less,
[0033] R: 2.0at% or more and 6.5at% or less,
[0034] A: 0at% or more and 2at% or less,
[0035] Fe: 83 at% or more and 92 at% or less, and
[0036] Co: 1.5 at % or more and 6.5 at % or less.
[0037] The method for producing a sintered ferrite magnet of the present invention comprises: a molding step of molding the powder of the ferrite calcined body of the present invention to obtain a molded body; and a firing step of firing the molded body to obtain a sintered body.
[0038] In the method for producing a sintered ferrite magnet of the present invention, it is preferred that the calcined body is calcined at a temperature of 1250°C to 1350°C.
[0039] In the method for producing a sintered ferrite magnet of the present invention, it is preferred that the calcined body is calcined at a temperature of 1280°C to 1330°C.
[0040] In the method for producing a sintered ferrite magnet of the present invention, it is preferred that the calcined body is calcined at a temperature of 1290°C to 1320°C.
[0041] In the method for producing a sintered ferrite magnet of the present invention, it is preferred that the calcined body is calcined in a rotary kiln.
[0042] The method for producing a sintered ferrite magnet of the present invention preferably further comprises a step of adding SiO2 in an amount greater than 0 mass % and not more than 1.5 mass % relative to 100 mass % of the calcined body after the calcined body preparation step and before the molding step.
[0043] In the method for producing a sintered ferrite magnet of the present invention, it is preferred that after the calcined body preparation step and before the molding step, a step of adding CaCO3 in an amount greater than 0 mass % and less than 1.5 mass % in terms of CaO relative to 100 mass % of the calcined body is further included.
[0044] In the method for producing a sintered ferrite magnet of the present invention, it is preferred that the step of adding 2 mass % or less of Cr2O3 based on 100 mass % of the calcined body is further included after the calcined body preparation step and before the molding step.
[0045] Effects of the Invention
[0046] According to the present invention, it is possible to provide a ferrite calcined body capable of obtaining a ferrite sintered magnet having high magnetic properties, and a method for producing a ferrite sintered magnet using the ferrite calcined body. DETAILED DESCRIPTION
[0047] 1. Ferrite pre-sintering
[0048] The ferrite calcined body of the present invention comprises: a ferrite phase having a hexagonal M-type magnetoplumbite structure containing metal elements of Ca, R, A, Fe and Co (R is at least one rare earth element, La is an element that must be contained, and A is Sr and / or Ba); and a spinel ferrite phase containing Co, and the ferrite calcined body contains 70% by mass or more and less than 100% by mass of the ferrite phase and more than 0% by mass and less than 30% by mass of the spinel ferrite phase.
[0049] The calcined ferrite body of the present invention further contains an orthoferrite phase in an amount of more than 0% by mass and less than 3% by mass, and does not substantially contain a hematite phase.
[0050] The main phase constituting the calcined ferrite is a ferrite phase having a hexagonal magnetoplumbite type (M type) structure. Generally, magnetic materials, especially sintered magnets, are defined as being composed of a variety of compounds.
[0051] “Having a hexagonal magnetoplumbite type (M type) structure” means that an X-ray diffraction pattern mainly having a hexagonal magnetoplumbite type (M type) structure is observed in X-ray diffraction measurement of calcined ferrite powder under general conditions.
[0052] The ferrite phase contained in the calcined ferrite body is 70 mass % or more and less than 100 mass %. When it is less than 70 mass %, high Br and H cannot be obtained. cj In the case of 100 mass %, high magnetic properties cannot be obtained.
[0053] Composition: (A m Fe 3-m The spinel ferrite phase of )O4 (wherein A is Co, Mn, Ni, Cu, Zn, Ca, etc.) is a phase having an equiaxed spinel structure. The ratio of the spinel ferrite phase contained in the calcined ferrite body is greater than 0 mass % and less than 30 mass %. In the case of 0 mass %, high H cj When the content of Br and H is greater than 30% by mass, high Br and H cj The content is preferably 5% by mass or more and 30% by mass or less, more preferably 5% by mass or more and 25% by mass or less, and still more preferably 10% by mass or more and 20% by mass or less.
[0054] The orthoferrite phase (LaFeO3, etc.) is a phase having a perovskite structure and is a multiphase in the ferrite calcined body of the present invention, but when the content is greater than 0 mass % and less than 3 mass %, it has almost no effect on the magnetic properties. When the content is more than 3 mass %, the proportion of the multiphase increases (the proportion of the ferrite phase decreases), so high magnetic properties cannot be obtained.
[0055] The hematite phase (α-Fe2O3) is a multiphase in the ferrite calcined body of the present invention. The ferrite calcined body of the present invention does not substantially contain the hematite phase. "Substantially not containing" means that the presence cannot be confirmed in X-ray diffraction. When the ferrite calcined body contains the hematite phase, it will lead to a significant decrease in magnetic properties (especially saturation magnetization).
[0056] In addition, the metal elements contained in each phase can be measured by EDS (energy dispersive X-ray spectroscopy) analysis, for example, using FE-SEM (field emission scanning electron microscope). The ferrite phase of the present invention contains Ca, R, A, Fe and Co. When the total amount of each element (the total amount of each element of Ca, R, A, Fe and Co) is set to 100at%, the composition ratio is:
[0057] Ca: 2.0 at% or more and 6.5 at% or less,
[0058] R: 2.0at% or more and 6.5at% or less,
[0059] A: 0at% or more and 2at% or less,
[0060] Fe: 83 at% or more and 92 at% or less, and
[0061] Co: 1.5 at % or more and 6.5 at % or less.
[0062] The content of Ca is preferably 2.0 at % or more and 6.5 at % or less. When the content is less than 2.0 at % or more than 6.5 at %, high magnetic properties cannot be obtained.
[0063] The content of R is preferably 2.0 at% or more and 6.5 at% or less. When the content is less than 2.0 at% or greater than 6.5 at%, high magnetic properties cannot be obtained. R is at least one of the rare earth elements, and La is an element that must be contained. The content of rare earth elements other than La is preferably less than 50% of the total amount of R in terms of atomic ratio.
[0064] The content of the A element is preferably 0 at% or more and 2 at% or less. The A element is Sr and / or Ba. Although the effect of the present invention is not impaired even if the A element is not contained, by adding the A element, the crystals in the calcined body are refined and the aspect ratio is reduced, so that the effect of further improving the magnetic properties can be obtained. When the A element exceeds 2.0 at%, high magnetic properties cannot be obtained.
[0065] The Fe content is preferably 83 at % or more and 92 at % or less. If it is less than 83 at % or more than 92 at %, high magnetic properties cannot be obtained.
[0066] The content of Co is preferably 1.5 at % or more and 6.5 at % or less. If the content of Co is less than 1.5 at % or more than 6.5 at %, high magnetic properties cannot be obtained.
[0067] In addition, the spinel ferrite phase contains Ca, Fe, Co and Mn. When the total amount of each element (the total amount of each element of Ca, Fe, Co and Mn) is set to 100at%, the composition ratio is:
[0068] Ca: more than 0 at% and less than 10 at%,
[0069] Fe: 80 at% or more and 90 at% or less,
[0070] Co: 2 at% to 15 at% and
[0071] Mn: more than 0 at % and 5 at % or less.
[0072] The content of Ca is preferably greater than 0 at % and less than 5 at %. When less than 2.0 at % or greater than 6.5 at %, high magnetic properties cannot be obtained.
[0073] The content of the Fe element is preferably 80 at % or more and 90 at % or less. When it is less than 80 at % or more than 90 at %, high magnetic properties cannot be obtained.
[0074] The content of the Co element is preferably 2 at % or more and 15 at % or less. When it is less than 1.5 at % or more than 6.5 at %, high magnetic properties cannot be obtained.
[0075] The content of the Mn element is preferably greater than 0 at % and less than 5 at %. When it is 0 at % or greater than 5 at %, high magnetic properties cannot be obtained.
[0076] Mn is contained in the Fe compound as the raw material powder as an inevitable impurity. When Mn is contained in the ferrite phase, it leads to a decrease in magnetic properties, but by making the Mn content in the spinel ferrite phase greater than the Mn content in the ferrite phase, high magnetic properties can be obtained. It is more preferred that the ferrite phase does not contain Mn and is only contained in the spinel ferrite phase. It should be noted that Mn is not limited to the case where it is contained as an inevitable impurity, but also includes the case where it is actively added.
[0077] The atomic ratio of metal elements in the entire ferrite calcined body of the present invention including a ferrite phase and a spinel ferrite phase can be expressed as follows in the form of a general formula.
[0078] In the general formula representing the atomic ratio of metal elements Ca, R, A, Fe and Co (R is at least one rare earth element, La is an element that must be contained, and A is Sr and / or Ba): Ca 1-x-y R x A y Fe 2n-z Co z In the above, x, y and z, and n (2n is a molar ratio, expressed as 2n = (Fe + Co) / (Ca + R + A)) satisfy the following formula:
[0079] 0.3≤1-x-y≤0.65,
[0080] 0.3≤x≤0.65,
[0081] 0≤y≤0.2,
[0082] 0.25≤z≤0.65, and
[0083] 4.5≤n≤7,
[0084] The content of Mn is more than 0 mass % and 0.5 mass % or less in terms of MnO.
[0085] It should be noted that the above general formula is expressed by the atomic ratio of metal elements, but the composition containing oxygen (O) is expressed by the general formula: Ca 1-x-y R x A y Fe 2n-z Co z O α The molar number α of oxygen is basically α=19, and the valences of Fe and Co will differ depending on the values of x, y and z, or n. In addition, the ratio of oxygen to the metal element will also change due to oxygen vacancies during firing in a reducing atmosphere, changes in the valence of Fe in the ferrite phase, changes in the valence of Co, etc. Therefore, the actual atomic ratio α of oxygen sometimes deviates from 19. For this reason, in the present invention, the composition is expressed by the atomic ratio of the metal element that is easiest to determine the composition.
[0086] Next, an example of the method for producing a sintered ferrite magnet of the present invention including the method for producing the calcined ferrite powder of the present invention described above will be described.
[0087] 2. Ferrite sintered magnet manufacturing method
[0088] As raw material powder, compounds such as oxides, carbonates, hydroxides, nitrates, chlorides, etc. of various metals can be used regardless of the valence. It can also be a solution in which the raw material powder is dissolved. As compounds of Ca, carbonates, oxides, chlorides, etc. of Ca can be mentioned. As compounds of R, rare earth oxides such as La2O3, rare earth hydroxides such as La(OH)3, rare earth carbonates such as La2(CO3)3·8H2O, etc. can be mentioned. As compounds of element A, carbonates, oxides, chlorides, etc. of Sr and / or Ba can be mentioned. As compounds of Fe, iron oxide, iron hydroxide, iron chloride, rolling scale, etc. can be mentioned. As compounds of Co, oxides such as CoO and CO3O4, hydroxides such as CoOOH and Co(OH)2, carbonates such as CoCO3, and alkaline carbonates such as m2CoCO3·m3Co(OH)2 / m4H2O (m2, m3, m4 are positive numbers) can be mentioned. It should be noted that Mn may be contained in the Fe compound as an inevitable impurity or an additive.
[0089] In order to promote the reaction during pre-calcination, as required, a compound containing B (boron) such as B2O3 or H3BO3 may be added in an amount of about 1 mass %. In particular, the addition of H3BO3 is effective in improving the magnet properties. The addition amount of H3BO3 is preferably less than 0.3 mass %, and most preferably about 0.1 mass %. Since H3BO3 also has the effect of controlling the shape and size of the grains during firing, it can be added after pre-calcination (before micro-crushing or before firing), or it can be added in both time periods before and after pre-calcination.
[0090] The raw material powders satisfying the above-mentioned components and compositions of the ferrite calcined body of the present invention are mixed to prepare mixed raw material powders. The raw material powders can be prepared by either a wet method or a dry method. When stirred with a medium such as a steel ball, the raw material powders can be mixed more uniformly. In the case of a wet method, water is preferably used as the dispersion medium. For the purpose of improving the dispersibility of the raw material powders, known dispersants such as ammonium polycarboxylate and calcium gluconate can be used. The mixed raw material slurry can be calcined directly or after the raw material slurry is dehydrated.
[0091] The mixed raw material powder obtained by dry mixing or wet mixing is heated in a continuous or intermittent electric furnace or gas furnace, etc., to form a hexagonal magnetoplumbite-type (M-type) ferrite compound by solid phase reaction. This process is called "pre-calcination" and the obtained compound is called "pre-calcined body".
[0092] For example, in the case of pre-firing using a rotary kiln as a continuous gas furnace, when the pre-firing temperature is less than 1250°C, the amount of spinel ferrite phase formed in the pre-firing body is insufficient, so the magnetic properties are reduced. On the other hand, when the pre-firing temperature is greater than 1350°C, the spinel ferrite phase exceeds 30% by mass, so the magnetic properties are reduced. Therefore, the pre-firing temperature is preferably a temperature of 1250°C to 1350°C. It is more preferably 1280°C to 1330°C, and even more preferably 1290°C to 1320°C.
[0093] In the pulverizing step, the calcined body is pulverized (coarsely pulverized) by a hammer mill or the like, and then pulverized (finely pulverized) by a vibration mill, a jet mill, a ball mill, an ultrafine grinding mill, or the like to prepare a pulverized powder. The average particle size of the pulverized powder is preferably about 0.4 μm to 1.2 μm. When attention is paid to the improvement of magnetic properties, it is preferably about 0.4 μm to 0.7 μm. When attention is paid to manufacturing costs (shortening pulverization time, shortening stamping cycle, etc.), it is preferably about 0.7 μm to 1.2 μm. It should be noted that in the present invention, the value measured by an air permeation method using a powder specific surface area measuring device (e.g., SS-100 manufactured by Shimadzu Corporation) is referred to as the average particle size (average particle size) of the powder.
[0094] The pulverizing process may be either dry pulverizing or wet pulverizing, or the two may be used in combination. In the case of wet pulverizing, water and / or a non-aqueous solvent (acetone, ethanol, xylene and other organic solvents) are used as a dispersion medium. Typically, a slurry containing water (dispersion medium) and a calcined body is generated. A known dispersant and / or surfactant may be added to the slurry in an amount of 0.2 to 2% by mass in terms of solid content ratio. The slurry may also be concentrated after wet pulverization.
[0095] The ferrite calcined body powder of the present invention can be obtained through the above-mentioned steps. Next, the method for producing the ferrite sintered magnet of the present invention is described.
[0096] In the molding process, the slurry after the pulverization process is pressed and molded in a magnetic field or a non-magnetic field while removing the dispersion medium. By pressing and molding in a magnetic field, the crystal orientation of the powder particles can be arranged (oriented) regularly, which significantly improves the magnetic properties. In addition, in order to improve the orientation degree, 0.1 to 1% by mass of a dispersant and a lubricant can be added to the slurry before molding. In addition, before molding, the slurry can be concentrated as needed. Concentration is preferably performed by centrifugation, a filter press, etc.
[0097] After the above-mentioned calcination step and before the molding step, a sintering aid is added to the calcined body or its pulverized powder. As a sintering aid, only SiO2 can be added, or both SiO2 and CaCO3 can be added, or Cr2O3 can be added in addition to SiO2 and CaCO3. The amount of SiO2 added is preferably greater than 0% by mass and less than 1.5% by mass relative to 100% by mass of the calcined body or its pulverized powder to be added. In the case where no SiO2 is added, H cJ The amount of SiO2 added is more preferably 0.4 to 0.7 mass %.
[0098] The amount of CaCO3 added is preferably greater than 0% by mass and less than 1.5% by mass in terms of CaO relative to 100% by mass of the calcined body or its pulverized powder to be added. cJ The amount of CaCO3 added is more preferably 0.4 mass % or more and 0.06 mass % or less.
[0099] The amount of Cr2O3 added is preferably 2% by mass or less relative to 100% by mass of the calcined body or its pulverized powder to be added. In the case of more than 2% by mass, Br is significantly reduced. The amount of Cr2O3 added is more preferably 1.5% by mass or less.
[0100] The sintering aid can be added by, for example, adding it to the calcined body obtained by the calcining step and then performing the pulverizing step, adding it during the pulverizing step, or adding it to the finely pulverized powder after the pulverizing step and mixing it before performing the molding step. As a sintering aid, in addition to SiO2, CaCO3 and Cr2O3, Al2O3 and the like can also be added.
[0101] It should be noted that in the present invention, the addition amount of CaCO3 is expressed by conversion to CaO. The addition amount of CaCO3 can be obtained by the formula: (molecular weight of CaCO3 × addition amount in CaO conversion) / molecular weight of CaO. For example, when 0.5 mass % of CaCO3 is added in CaO conversion, {(40.08[atomic weight of Ca]+12.01[atomic weight of C]+48.00[atomic weight of O×3]=100.09[molecular weight of CaCO3])×0.5 mass %[addition amount in CaO conversion]} / (40.08[atomic weight of Ca]+16.00[atomic weight of O]=56.08[molecular weight of CaO])=0.892 mass %[addition amount of CaCO3].
[0102] The molded body obtained by press molding is fired (sintered) after degreasing as needed. For firing, an electric furnace, a gas furnace, etc. are used. For firing, it is preferably carried out in an atmosphere with an oxygen concentration of 10 volume % or more. More preferably, it is 20 volume % or more, and most preferably, it is 100 volume %. The firing temperature is preferably 1150° C. to 1250° C. The firing time is preferably 0 hours (without holding at the firing temperature) to 2 hours.
[0103] When heating up the firing process, it can be in the temperature range from room temperature to 1100°C, the temperature can be raised at an average heating rate of more than 400°C / hour and less than 1000°C / hour, and in the temperature range from 1100°C to the firing temperature, the temperature can be raised at an average heating rate of more than 1°C / minute and less than 10°C / minute. In addition, when cooling down after the firing time of the firing process is maintained (including the case where it is not maintained), when the average cooling rate in the temperature range from the firing temperature to 800°C is set to more than 300°C / hour, the magnetic properties are further improved, and thus it is preferred. It should be noted that although these effects can be obtained by only using the above-mentioned cooling rate, it is more preferred to use both the above-mentioned heating rate and the cooling rate. In addition, when describing the temperature, it refers to the temperature of the heat-treated object. The temperature is measured by contacting the R thermocouple with the heat-treated object in the firing furnace.
[0104] After the firing step, the ferrite sintered magnet is finally manufactured through known manufacturing processes such as processing steps, cleaning steps, and testing steps.
[0105] Example
[0106] The present invention is further described in detail below by way of examples, but the present invention is not limited thereto.
[0107] Experimental Example 1
[0108] To become the general formula Ca 0.5 La 0.5 Fe 10.1 Co 0.3 CaCO3 powder, La2O3 powder, Fe2O3 powder, and Co3O4 powder were weighed according to a prescribed composition, and 0.12% by mass of H3BO3 powder was added to 100% by mass of the weighed powders, and the mixture was mixed with an ultrafine mill to obtain a mixed slurry. It should be noted that Mn is contained in the Fe2O3 powder as an inevitable impurity.
[0109] The obtained mixed slurry was pre-calcined in the air at the pre-calcination temperature shown in Table 1 to obtain 8 types of pre-calcined bodies. Samples No. 1 to 7 were pre-calcined in a rotary kiln, and as a comparative example, Sample No. 8 was pre-calcined in a box furnace (intermittent electric furnace). Then, each of the obtained pre-calcined bodies was coarsely pulverized with a small mill to obtain 8 types of coarsely pulverized powders.
[0110] The phase ratios (mass %) of the constituent phases contained in the eight kinds of coarsely pulverized powders were obtained. The results are shown in Table 1. It should be noted that the phase ratios were obtained by performing X-ray diffraction using an X-ray diffraction apparatus (D8 ADVANCE TXS manufactured by Bruker AXS) and analyzing the obtained X-ray diffraction pattern using the full spectrum fitting (Rietveld) method.
[0111] CaCO3 (added amount calculated as CaO) and SiO2 shown in Table 1 were added to 100% by mass of the 8 kinds of coarsely pulverized powders, and finely pulverized by wet ball milling using water as a dispersion medium to obtain finely pulverized slurries. Finely pulverized to average particle sizes (measured by air permeation method using a powder specific surface area measuring device (Shimadzu Corporation SS-100)) were shown in Table 1.
[0112] Each finely pulverized slurry was molded by applying a magnetic field of about 1 T and a pressure of about 2.4 MPa using a parallel magnetic field molding machine (longitudinal magnetic field molding machine) in which the pressurizing direction and the magnetic field direction were parallel while removing the dispersion medium, to obtain 8 types of molded bodies.
[0113] The obtained molded bodies were inserted into a sintering furnace, and the temperature was raised to 1100°C at a heating rate of 400°C / hour in the atmosphere, and then raised to the firing temperature shown in Table 1 at a heating rate of 1°C / minute. The fired bodies were then fired for 1 hour, and then cooled to room temperature at an average cooling rate of 300°C / hour from the firing temperature shown in Table 1 while air was supplied at a rate of 10 L / minute. Thus, 8 kinds of ferrite sintered magnets were obtained. The Br and H cJ and H k / H cJ The measurement results are shown in Table 1. In Table 1, samples No. 1 to 7 without an * on the right side of the sample number No. are experimental examples based on the embodiment of the present invention, and sample No. 8 with an * is an experimental example (comparative example) that does not meet the requirements of the embodiment of the present invention. It should be noted that H in Table 1 k In the second quadrant of the J (magnetic polarization intensity)-H (magnetic field intensity) curve, J is 0.95×J r (J r The H value at the position when Jr is the remanence value (Br).
[0114] [Table 1]
[0115]
[0116] The magnetic properties of sample No. 8 using calcined powder containing 0 mass % of spinel ferrite phase are compared with the magnetic properties of samples No. 1 to 7 using calcined powder containing spinel ferrite phase. Samples No. 1 to 7 can obtain the same degree of properties as Br, and H cJ Furthermore, when the spinel ferrite phase shown in Samples No. 2 to 6 is 10 mass % or more and 20 mass % or less, H cJ The value can reach over 420kA / m, achieving very high characteristics.
[0117] In addition, the results of Samples No. 1 to 7 show that the calcination temperature for obtaining high magnetic properties is 1250° C. to 1350° C. The results of Samples No. 2 to 6 show that the calcination temperature for obtaining higher magnetic properties is 1290° C. to 1320° C.
[0118] Experimental Example 2
[0119] To become the general formula Ca 0.5 La 0.5 Fe 10.1 Co 0.3CaCO3 powder, La2O3 powder, Fe2O3 powder, and Co3O4 powder were weighed according to a prescribed composition, and 0.12% by mass of H3BO3 powder was added to 100% by mass of the weighed powders, and the mixture was mixed with an ultrafine mill to obtain a mixed slurry. It should be noted that Mn is contained in the Fe2O3 powder as an inevitable impurity.
[0120] The obtained mixed slurry was calcined in the air using a rotary kiln at the calcination temperature shown in Table 2 to obtain 10 types of calcined bodies. Then, each of the obtained calcined bodies was coarsely pulverized using a small mill to obtain 10 types of coarsely pulverized powders.
[0121] The phase ratios (mass %) of the constituent phases contained in the 10 kinds of coarsely pulverized powders were determined and confirmed in the same manner as in Experimental Example 1. It was confirmed that the samples No. 9 to 13 having a pre-sintering temperature of 1310° C. contained 12 mass % of the spinel ferrite phase, and the samples No. 14 to 18 having a pre-sintering temperature of 1330° C. contained 25 mass % of the spinel ferrite phase.
[0122] In order to study the composition ratio (at%) of each element when the total amount of each element contained in the ferrite phase of the coarsely pulverized powder of Sample No. 9 to 18 (the total amount of each element of Ca, La, Fe and Co) is set to 100at% and the composition ratio (at%) of each element when the total amount of each element contained in the spinel ferrite phase (the total amount of each element of Ca, Fe, Co and Mn) is set to 100at%, EDS (energy dispersive X-ray spectroscopy) analysis and measurement were performed using Fe-SEM (field emission scanning electron microscope). The results are shown in Table 2.
[0123] [Table 2]
[0124]
[0125] It can be seen that in all samples No. 9 to 18, Mn is contained in the spinel ferrite phase and Mn is not contained in the ferrite phase. It is believed that by forming a spinel ferrite phase in the calcined body, Mn that causes a decrease in magnetic properties is contained in the spinel ferrite phase, which has the effect of suppressing the inclusion of Mn in the ferrite phase, and as a result, a ferrite sintered magnet with high magnetic properties is obtained.
[0126] Experimental Example 3
[0127] To become the general formula Ca 0.5 La 0.5 Fe 10.1 Co 0.3CaCO3 powder, La2O3 powder, Fe2O3 powder, and Co3O4 powder were weighed according to a prescribed composition, and 0.12% by mass of H3BO3 powder was added to 100% by mass of the weighed powders, and the mixture was mixed with an ultrafine mill to obtain a mixed slurry. It should be noted that Mn is contained in the Fe2O3 powder as an inevitable impurity.
[0128] The obtained mixed slurry was pre-calcined in the air at the pre-calcination temperature shown in Table 3 to obtain a pre-calcined body. All slurries were pre-calcined in a rotary kiln. Then, each of the obtained pre-calcined bodies was coarsely pulverized in a small mill to obtain a coarsely pulverized powder.
[0129] The phase ratio (mass %) of the constituent phase contained in the coarsely pulverized powder was determined. The results are shown in Table 3. The phase ratio of the constituent phase was determined in the same manner as in Experimental Example 1.
[0130] CaCO3 (added amount calculated as CaO) and SiO2 shown in Table 3 were added to 100% by mass of the coarsely pulverized powder, and finely pulverized using a wet ball mill with water as a dispersion medium to obtain 7 kinds of finely pulverized slurries. The finely pulverized slurries were pulverized to an average particle size (measured in the same manner as in Experimental Example 1) as shown in Table 3.
[0131] Using each finely pulverized slurry, molding was performed in the same manner as in Experimental Example 1 to obtain 7 types of molded bodies.
[0132] The obtained molded bodies were placed in a sintering furnace, and the temperature was raised to 1100°C at a heating rate of 400°C / hour in the air, and then raised to the firing temperature shown in Table 3 at a rate of 1°C / minute, and then fired for 1 hour. The molded bodies were cooled from the firing temperature shown in Table 3 to room temperature at an average cooling rate of 300°C / hour while air was supplied at a rate of 10 L / minute, thereby obtaining 7 kinds of ferrite sintered magnets. The Br and H cJ and H k / H cJ The measurement results are shown in Table 3.
[0133] [Table 3]
[0134]
[0135] According to the results of samples No. 19 to 25, since the calcination temperature was within the range of 1290°C to 1320°C, the spinel ferrite phase was 10% to 20% by mass, and H cJ Very high characteristics with values up to 420kA / m or more.
[0136] Experimental Example 4
[0137] To become the general formula Ca 0.5 La 0.5 Fe 10.1 Co 0.3 The CaCO3 powder, La2O3 powder, Fe2O3 powder, and Co3O4 powder were weighed according to a prescribed composition, and 0.12% by mass of H3BO3 powder was added to the weighed powders (100% by mass), and the mixture was mixed with an ultrafine mill to obtain a mixed raw material slurry. It should be noted that Mn is contained in the Fe2O3 powder as an inevitable impurity.
[0138] The obtained mixed raw material slurry was pre-calcined in the air at the pre-calcination temperature shown in Table 4 to obtain 18 kinds of pre-calcined bodies. All of them were pre-calcined in a rotary kiln. Then, each of the obtained pre-calcined bodies was coarsely pulverized to obtain 18 kinds of coarsely pulverized powders.
[0139] The ratios (%) of the constituent phases contained in the 18 kinds of coarsely pulverized powders were determined. The results are shown in Table 4. The phase ratios were determined in the same manner as in Experimental Example 1.
[0140] CaCO3 (the amount added is calculated as CaO), SiO2 and Cr2O3 shown in Table 3 were added to 100% by mass of the 18 kinds of coarsely pulverized powders, and finely pulverized using a wet ball mill with water as a dispersion medium to obtain finely pulverized slurries. Finely pulverized to an average particle size (measured in the same manner as in Experimental Example 1) respectively became the particle sizes shown in Table 4.
[0141] Each finely pulverized slurry was used to perform molding in the same manner as in Experimental Example 1, thereby obtaining 18 types of molded bodies.
[0142] Each of the obtained molded bodies was inserted into a sintering furnace, and in the atmosphere, the temperature was raised to 1100°C at a heating rate of 400°C / hour, and then raised to the firing temperature shown in Table 1 at a rate of 1°C / minute, and then fired for 1 hour, and then cooled from the firing temperature shown in Table 4 to 800°C at an average cooling rate of 300°C / hour while air was supplied at a rate of 10 L / minute, and then cooled to room temperature over 8.5 hours, thereby obtaining 18 kinds of ferrite sintered magnets. The Br and H cJ and H k / H cJ The measurement results are shown in Table 4.
[0143] [Table 4]
[0144]
[0145] The results of samples No. 26 to 43 show that the addition of Cr2O3 in addition to CaCO3 and SiO2 can achieve higher H cJ In either case, the calcination temperature is within the range of 1290°C to 1320°C, so the spinel ferrite phase is 10% to 20% by mass, and H cJ The value is 420kA / m or more, which is a very high characteristic.
[0146] Industrial Applicability
[0147] According to the present invention, a ferrite sintered magnet having high magnetic properties can be obtained, and thus the provided ferrite sintered magnet can be suitably used in various motors and the like.
Claims
1. A ferrite calcined body, characterized in that: It has ferrite phase and spinel ferrite phase. The ferrite phase contains metal elements of Ca, R, A, Fe and Co, and has a hexagonal M-type magnetite structure, wherein R is at least one rare earth element, La is a necessary element, and A is Sr and / or Ba. When the total amount of Ca, R, A, Fe and Co is set to 100 at%, the composition ratio is: Ca: 2.0 at% or more and 6.5 at% or less, R: 2.0at% or more and 6.5at% or less, A: 0at% or more and 2at% or less, Fe: 83 at% or more and 92 at% or less, and Co: 1.5 at% or more and 6.5 at% or less, The spinel ferrite phase contains Ca, Fe, Co and Mn. When the total amount of Ca, Fe, Co and Mn is set to 100 at%, the composition ratio is: Ca: more than 0 at% and less than 10 at%, Fe: 80 at% or more and 90 at% or less, Co: 2 at% to 15 at% and Mn: more than 0 at% and less than 5 at%, The ferrite calcined body contains 70 mass % or more and less than 100 mass % of the ferrite phase and 10 mass % or more and 20 mass % or less of the spinel ferrite phase.
2. The ferrite calcined body according to claim 1, characterized in that: The general formula representing the atomic ratio of metal elements Ca, R, A, Fe and Co in the ferrite calcined body is: Ca 1-x- y R x A y Fe 2n-z Co z In the formula, x, y, z and n satisfy the following formula: 0.3≤1-x-y≤0.65, 0.3≤x≤0.65, 0≤y≤0.2, 0.25≤z≤0.65, and 4.5≤n≤7, Wherein, R is at least one rare earth element, La is an element that must be contained, A is Sr and / or Ba, 2n is a molar ratio, expressed as 2n = (Fe + Co) / (Ca + R + A), The ferrite calcined body contains more than 0 mass % and 0.5 mass % or less of Mn in terms of MnO.
3. The ferrite calcined body according to claim 1, characterized in that: The calcined body contains Mn, and the Mn content in the spinel ferrite phase is greater than the Mn content in the ferrite phase.
4. The ferrite calcined body according to claim 1, characterized in that: Mn is contained only in the spinel ferrite phase.
5. The ferrite calcined body according to claim 1, characterized in that: Furthermore, the La orthoferrite phase is contained in an amount of more than 0 mass % and less than 3 mass %.
6. The ferrite calcined body according to claim 1, characterized in that: It contains virtually no hematite phase.
7. A method for producing a ferrite sintered magnet, characterized in that: include: A step of molding a calcined body by molding the pulverized powder of the ferrite calcined body according to any one of claims 1 to 4 which has been calcined at a temperature of 1290°C to 1320°C in a rotary kiln; and a step of firing the calcined body to obtain a sintered body.
8. The method for producing a sintered ferrite magnet according to claim 7, wherein: The method further includes the step of adding SiO 2 in an amount greater than 0 mass % and not more than 1.5 mass % relative to 100 mass % of the pulverized powder of the calcined ferrite before the molding step.
9. The method for producing a sintered ferrite magnet according to claim 7, wherein: The method further includes the step of adding CaCO 3 in an amount of more than 0 mass % and 1.5 mass % or less in terms of CaO relative to 100 mass % of the pulverized powder of the calcined ferrite before the molding step.
10. The method for producing a sintered ferrite magnet according to claim 7, wherein: The method further includes the step of adding 2 mass % or less of Cr 2 O 3 to the pulverized powder of the calcined ferrite prior to the molding step, based on 100 mass % of the pulverized powder of the calcined ferrite.
Citation Information
Patent Citations
Method for manufacturing ferrite sintered magnet
JP2020155609A
Oxide magnetic material
CN101351853A
Permanent magnet and method for preparation thereof
CN1462453A